(Il)logical knowledge management a guide to knowledge management in the 21st century - Weed-Schertzer, Beverly (Emerald points., 2020)
In today's world, strategic knowledge management is a critical practice for all businesses seeking to protect its assets and produce intelligible and useable information. However, formally implementing a comprehensive knowledge management infrastructure to support an organization--enabling businesses to create, protect, and collaborate through knowledge--is often easier said than done. How do businesses adapt to the evolving challenges of knowledge management, and what best-practice tips are actually based on common misconceptions? From social media and collaborative information systems to new technological developments in cognitive computing and artificial intelligence, (Il)logical Knowledge management dives deep into the sometimes less-than-logical approaches to knowledge management that pervade present practice. It goes beyond existing understanding of how knowledge is transferred, stored, and shared to address the key challenges organizations face in overseeing their business' knowledge management efforts. In finding the logical by way of the illogical, Beverly Weed-Schertzer highlights opportunities in both the public and private sectors to improve the efficacy and extent of knowledge management infrastructure. -- Publisher's note.